Teriparatide in a patient with severe osteoporosis, hypoparathyroidism and thalassemia major - Graziani A; Cannito M; Putti MC; Camozzi V (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2022)
β-Thalassemia Major (TM) is a form of beta-thalassemias. TM complications include, among others, osteoporosis, whose frequency, among TM patients, varies from 13.6% to 50%. The overall etiological mechanisms of TM-related osteoporosis remain unclarified. The primary approach to osteoporosis in patients with TM is the management of TM and its complications and the use of antiresorptive agents, such as Bisphosphonates (BPs), as the first line-drug of treatment. In this article, we present the case of 45 years old-woman with TM and severe osteoporosis, with multiple fractures, albeit the assumption of BPs for many years. The anti-fracture efficacy and safety of BPs are not well-established in TM patients. Data suggest that etidronate and zoledronic acid should be considered as first-line agents in the management of TM- associated osteoporosis. Regarding Teriparatide (TP), there are only a few case reports published about its use in TM patients. It is also noticed that, at the dismission of TP therapy, its benefits are rapidly lost. Finally, regarding romosozumab, our patient presents a significant cardiovascular risk due to the presence of insulin-treated Diabetes Mellitus (DM) and TM-related cardiomyopathy, suggesting we avoid this drug. This case report shows that the therapy of osteoporosis in patients with TM remains an open problem. TM patients often present multiple comorbidities which create limitations to osteoporosis's treatment. Moreover, these comoboridites are often unavoidable risk factors for osteoporosis.